Characterization and Differentiation of Chemical Heterogeneity in Humic Substances by Continuous Intrinsic Proton Affinity Distribution - Zhang Hongxia; Dong Wenming; Huang Meide; Tao Zuyi (Adsorption Science & Technology)
The chemical heterogeneity of proton binding on humic substances was studied via continuous intrinsic proton affinity distributions calculated using the condensation approximation from the master curves for two soil fulvic acids (FAs), one soil humic acid (HA) and one fulvic acid obtained from weathered coal. The master curves, i.e. plots of θ T,H (the overall protonation degree) versus Hs (the proton concentration in the diffuse double layer), were obtained from potentiometric titration curves at three ionic strengths. The value of Hs was calculated using an electrical double-layer model in which the humic substances were considered as rigid impermeable spheres. For all four samples, the proton affinity distributions were characterized by a few peaks with peak positions in the range 4–5.5. The similarities and differences between the samples studied were discussed.